Grace Baptist church information system (GBCIS) - Ong, Chin Cheng (Universiti Malaysia Sarawak, (UNIMAS), 2006)
Information Technology has changed made a great impact in almost every aspect of human life. It is now an integrated part of human life. The benefit of Information Technology lies with its ability to automate repetitive tasks with more efficiency than human Grace Baptist Church Information System (GBCIS) intends to handle the management of Grace Baptist Church 's membership system by systematically recording, retrieving and processing its member's records as a start. The purpose of this project is to lighten the workloads of those responsible for the management of information in the church, thus freeing them for other task. Literature reviews were performed to ascertain the current practice and technology available for the proposed System. Prototyping is used as the development methodology in this project. Usability Testing was then carried out through the use of System usability Scale (SUS) to gather user feedback. Suggestions for future enhancements are included to further enhance the future generations of GBCIS. The project is developed in Microsoft Visual Basic 6.0 Service Pack 6. with Microsoft Access Database as its database.